2020
DOI: 10.1007/978-3-030-25838-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Does Divorce Penalize Elderly Fathers in Receiving Help from Their Children? Evidence from Russia

Abstract: In times of increased pressure on welfare states, filial caregiving to elderly parents is becoming an increasingly important addition to state organised elderly care. However, certain life course events may cause the relationship between parents and their children to decline, impeding upward intergenerational support. We investigated the effect of divorce on the probability of receiving support from adult children, looking specifically at differences between mothers and fathers. Using Russian data from the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, differences in support by parents' gender seem to increase after separation. While transfers, contacts, and closeness between fathers and their adult children are often lower or less frequent if fathers separated, the associations between mother-children solidarity and mother's separation are rather mixed (Grundy, 2005;Kalmijn, 2007;2013;Maes et al, 2020). Accordingly, we pay attention to differences between mothers and fathers.…”
Section: Parental Separation and Intergenerational Supportmentioning
confidence: 99%
“…In addition, differences in support by parents' gender seem to increase after separation. While transfers, contacts, and closeness between fathers and their adult children are often lower or less frequent if fathers separated, the associations between mother-children solidarity and mother's separation are rather mixed (Grundy, 2005;Kalmijn, 2007;2013;Maes et al, 2020). Accordingly, we pay attention to differences between mothers and fathers.…”
Section: Parental Separation and Intergenerational Supportmentioning
confidence: 99%
“…Diverse family life courses have produced forms of relatedness (Silverstein and Giarrusso 2010 ) that can lead to late life exclusion (Gilligan et al 2018 ). There is evidence, for example, that across family life courses in which couples have divorced, older men are less likely than women to receive material support from children (Maes et al 2020 ). Siblings estranged over tensions in parent care may be unprepared to support each other in later life (Jensen et al 2020 ; Keating et al 2019 ).…”
Section: Framing the Research Agendamentioning
confidence: 99%
“…Logically enough, not only non-resident fathers demonstrate less care for their children than resident ones, also, in turn, children of divorced parents more rarely care for their elderly fathers than for their elderly mothers (Maes, Thielemans, & Tretyakova, 2020). In Jenkinson, Matsuo and Matthis (2020) study fathers with non-residential children below 18 reported lower life satisfaction than non-residential mothers.…”
Section: Literature Reviewmentioning
confidence: 99%